Coping with demographic change : a comparative view on education and local government in Germany and Poland /: a comparative view on education and local government in Germany and Poland. ([2015]) - Sackmann, Reinhold; Bartl, Walter; Jonda, Bernadette; Kopycka, Katarzyna; Rademacher, Christian
No abstract available